Differential item functioning of economics question papers of national examinations council in Delta state, Nigeria (2013)
This study attempted to detect item bias using differential item functioning approach in relation to gender (male and female) and school type (private and public schools). Using National Examinations Council (NECO) Economics questions for 2010. The research design employed in this study was a comparative research type of design. The study sample comprised students in Ethiope East local government area of Delta state. Four hundred and fourty seven (447) students were used. The test contains 60 items which was adminstered to the students. To detect items bias in relation to gender and school type, logistic regression was used; the result showed that there were item biases in terms of gender and school type. It was then recommended that items should be constructed in future taking cognizance of gender and school type.